2017
DOI: 10.21527/2237-6453.2017.39.171-202
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do Desempenho Ambiental do Aproveitamento do Biogás em Fecularias de Mandioca no Estado do Paraná

Abstract: ResumoO processo produtivo da mandioca gera resíduos com altas cargas orgânicas e componentes tóxicos. As indústrias desse setor tratam esses resíduos, na maioria das vezes, em lagoas de estabilização anaeróbias, nas quais se forma o biogás, um gás poluente que, se liberado para a atmosfera de forma indiscriminada, pode impactar no efeito estufa. O biogás, entretanto, pode ser recuperado dessas lagoas por meio da tecnologia de biodigestores e, por sua vez, aproveitado para alimentar as caldeiras em substituiçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…In the first one, environmental management or monitoring practices were evaluated and it was identified that the three starch plants studied carried out some environmental conservation actions, involving a reduction in the consumption of water, electricity, water reuse, and selective collection of industrial waste. For water, soil, and air resources, the benefits refer to the reduction of about 90% in the demand for firewood, a reduction of 34 thousand tons CO 2 equivalent due to the capture of methane gas generated in the first effluent treatment pond, as presented by Guimarães et al (2014). Lansche et al (2020) used the life cycle assessment (LCA) tool to compare different scenarios of cassava production and processing and concluded that environmental impacts can be reduced if the biogas resulting from the use of waste is used for production of electricity and heat.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the first one, environmental management or monitoring practices were evaluated and it was identified that the three starch plants studied carried out some environmental conservation actions, involving a reduction in the consumption of water, electricity, water reuse, and selective collection of industrial waste. For water, soil, and air resources, the benefits refer to the reduction of about 90% in the demand for firewood, a reduction of 34 thousand tons CO 2 equivalent due to the capture of methane gas generated in the first effluent treatment pond, as presented by Guimarães et al (2014). Lansche et al (2020) used the life cycle assessment (LCA) tool to compare different scenarios of cassava production and processing and concluded that environmental impacts can be reduced if the biogas resulting from the use of waste is used for production of electricity and heat.…”
Section: Results and Analysismentioning
confidence: 99%
“…Previous studies have analyzed the biodigester technology studied here, however, limited to a single dimension of sustainability (Guimarães et al 2014), respectively, its environmental performance and economic viability, with positive results that the technology is sustainable. Even so, there was a gap in the proposal of new models that add other aspects or dimensions, contemplate different realities, and allow a joint evaluation between performances.…”
Section: Introductionmentioning
confidence: 99%